Facile one-pot scalable strategy to engineer biocidal silver nanocluster assembly on thiolated PVDF membranes for water purification. Issue 45 (19th April 2016) - Sharma, Maya; Padmavathy, Nagarajan; Remanan, Sanjay; Madras, Giridhar; Bose, Suryasarathi
Abstract : Biofouling, due to bacterial growth and colonization, is a significant obstacle in water treatment that severely affects the membrane performance. Abstract : Biofouling, due to bacterial growth and colonization, is a significant obstacle in water treatment that severely affects the membrane performance. Nanofiltration effectively removes viruses and other pathogens but is an energy intensive process. Designing and developing low pressure driven membranes with potential antimicrobial and antibiofouling properties is a concern. Under this framework, biocidal silver nanoparticles based polymeric membranes with high content of silver on the membrane surface can control bacterial colonization. However, leaching of silver during water treatment may also lead to toxicity. In the present work, a unique strategy resulting in distinct surface assembly of silver nanoparticles was established on thiol functionalized PVDF membranes. Nanocluster assembly of silver nanoparticles on the PVDF membrane was obtained by esterification reaction between thioglycolic acid (TGA) and alkaline treated PVDF membrane (TGA–PVDF). On the other hand, by introducing thiol–ene chemistry between pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) and alkaline treated PVDF (PETMP–PVDF), well dispersed silver nanoparticles can be tailored on the membrane surface. The silver nanocluster assembly on TGA–PVDF membranes results in control leaching, as confirmed by inductively coupled plasma atomic emission spectroscopy (ICP) and X-ray photon spectroscopy (XPS) analysis in striking contrast to PETMP–PVDF. The trans-membrane flux was assessed and our results uncover that the designed membranes showed higher flux rate. These results have important implications in designing membranes for water purification and reveal the importance of the surface assembly of biocidal nanoparticles towards antibacterial properties.